2019
DOI: 10.1097/sap.0000000000001822
|View full text |Cite
|
Sign up to set email alerts
|

Distal Finger Reconstruction by Bilateral Lateral Hallux Osteo-onychocutaneous Free Flap

Abstract: Objective In this report, we present our experience on the use of bilateral lateral hallux osteo-onychocutaneous free flaps for reconstruction of distal finger and the aesthetic and functional results of this technique in a series of cases. Patients and Methods From February 2005 to May 2015, 7 patients underwent finger reconstruction distal to the distal interphalangeal joint using the bilateral lateral hallux osteo-onychocutaneous free flaps. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Even though the pedicle is short, there is no specific problem in vessel anastomosis. No large scars are left on the hands or feet [8,9]. This leads to cosmetic improvements and avoids prolonged surgical times.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the pedicle is short, there is no specific problem in vessel anastomosis. No large scars are left on the hands or feet [8,9]. This leads to cosmetic improvements and avoids prolonged surgical times.…”
Section: Discussionmentioning
confidence: 99%
“…The further improvements, described in the literature, in a wraparound fashion include the following: (1) extend proximally with a dorsalis pedis flap for the coverage of the dorsal finger; (2) combine with a second toe tibial flap for the coverage of the volar finger; (3) extract the dorsal nail-skin flap with a fibular hemipulp flap, supplied by the neurovascular bundle; (4) preserve the plantar triangular flap, instead of a few tibial strips 11 ; (5) sculpture the iliac bone graft into a conical contour to prevent bulging pulp 12 ; (6) dissect a great toe hemipulp flap with a second toe nail-skin flap for coverage of the distal finger; (7) combine ipsilateral second toe dorsal nail-skin flap with the contralateral second toe fibular flap for coverage of the distal finger 13 ; and (8) use bilateral lateral hallux osteo-onychocutaneous free flaps for reconstruction of the distal finger. 14 In the twist-toe technique for finger reconstruction, the tip of the distal phalanx could be taken with the nail to preclude nail deformity. 15 The toe-to-hand transfer had been used in past decades; its worse appearance and loss of toe contradict our experience.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the exposure of the nail root from 0.3 to 0.4 cm, although the appearance of the nail was restored, the normal length of the nail and finger was still missing because the defects of the nail bed and fingertip had not been restored. Wang et al [ 16 ] used bilateral free lateral hallux nail flap combined with the bone to treat seven distal interphalangeal joint defect cases with an average follow-up of 93.4 months. The results showed that the injured fingers had a good appearance and sensory and motor function.…”
Section: Discussionmentioning
confidence: 99%